Preparation method of automobile identification label

Through milling, anodizing and radial engraving, multi-layer color effects are formed and weather resistance is enhanced, which solves the problems of ink injection and ink removal in the existing OPC production process of automobile logos, and achieves efficient preparation and improvement of product quality.

CN119589305AActive Publication Date: 2025-03-11DONGGUAN ZHIXING ELECTRONICS HARDWARE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411771846.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing automotive label OEM production process has complexity and time-consuming problems in the ink injection and removal process of the concave areas, and problems such as color difference and uneven coating are inevitable, which affects product quality and production efficiency.

Method used

Multi-step processes such as milling, anodizing and radial engraving are adopted to form the first convex surface, the second convex surface and the concave surface through milling are then performed, and anodizing and radial engraving are formed to form a multi-layered color effect. The weather resistance and fading resistance are enhanced through the second anodizing, reducing the ink injection and ink removal process.

Benefits of technology

It realizes efficient preparation of automobile labels, solves the complexity and time-consuming problems of ink injection and ink removal processes, improves production efficiency and product quality, and does not require repeated printing or transfer processes, simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119589305A_ABST
    Figure CN119589305A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of signboard processing, in particular to a preparation method of an automobile signboard. Milling: machining one surface of the board body, and forming a first convex drawing surface, a second convex drawing surface and a concave drawing surface on the surface to obtain a milled part; cleaning and anodizing the milled part to form a first color oxidation film, and sealing holes to obtain a first anode part; performing first laser etching: performing laser etching on all the surfaces, except for the first convex pattern surface, the second convex pattern surface and the concave pattern surface, of the first anode part, so that the first color oxidation film is completely removed, and a first laser etching part is obtained; second laser etching: carrying out laser etching on a second convex pattern surface of the first laser etching piece to form a deep color layer so as to obtain a second laser etching piece; and the second anode is used for conducting anodic oxidation on the second laser carving piece, all the faces, except the concave pattern face and the first convex pattern face, of the second laser carving piece are plated with a layer of second-color oxidation film, hole sealing is conducted, the automobile identification label is obtained, and the production efficiency and quality of the automobile identification label are improved through the technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of identification plate processing, and more specifically, to a method for preparing an automobile identification plate. Background Art

[0002] As an important exterior decoration component, automobile logos are widely used in automobile manufacturing and the production of electronic products. As consumers' requirements for product appearance quality continue to increase, the production process of logos is also constantly improving. Traditional logos are mainly made through casting, stamping, spraying and other processes. Although these processes are mature, they have certain limitations in detail processing and color consistency. Especially for the high-end market, logos need to have higher precision, richer color expression and stronger weather resistance to meet increasingly stringent design requirements and technical standards.

[0003] In the existing logo and OEM production process, common methods include but are not limited to: 1) Casting and stamping: forming through molds, and then surface treatment such as painting, electroplating, etc., but this method is difficult to achieve complex patterns and fine color control; 2) Laser engraving: using a laser beam to carve the desired pattern on the surface of the card, and then painting, but the depth and accuracy of laser engraving are limited, and the cost is relatively high; 3) Spraying and screen printing: forming patterns on the surface of the card by spraying or screen printing, but these methods are difficult to handle details and are prone to problems such as color difference and uneven coating.

[0004] Although the above methods can meet the production needs of logo and OEM to a certain extent, there are still some obvious shortcomings. For example, when dealing with the problem of ink filling in the concave area, it is usually difficult to complete with automated equipment due to the small space. Manual operation is usually required, and repeated corrections and ink replenishment are required, which is time-consuming and has low production efficiency. In addition, the ink is prone to local adhesion during the deinking process, which makes deinking difficult. Increasing the deinking time will damage the anodized layer, affecting the product quality, and its color often does not meet the customer's requirements. Therefore, the existing logo and OEM production process is in urgent need of improvement to improve production efficiency and product quality. Summary of the invention

[0005] In order to improve the production efficiency and quality of automobile logo labels, the present application provides a method for preparing automobile logo labels.

[0006] A method for preparing a car logo plate comprises the following steps: Milling: processing one side of the plate body to form a first convex surface, a second convex surface and a concave surface on its surface to obtain a milled part; First anode: clean the milled part, then perform anodization to form a first color oxide film on the surface of the milled part, seal the hole, and obtain the first anode part; First laser engraving: laser engraving all surfaces of the first anode part except the first convex surface, the second convex surface and the concave surface, and removing all the first color oxide film formed thereon to obtain a first laser engraved part; Second laser engraving: laser engraving the second convex surface of the first laser engraved piece so that the second convex surface forms a dark color layer to obtain a second laser engraved piece; Second anode: anodize the second laser engraved piece, so that all surfaces of the second laser engraved piece except the concave surface and the first convex surface are coated with a second color oxide film, and the holes are sealed to obtain a car logo plate.

[0007] By adopting the above technical solution, efficient preparation of automobile logo labels is achieved, and the problem of complex and time-consuming ink filling and de-inking processes in the process is solved.

[0008] Specifically, milling processing: through precision processing of the brand body, the first convex surface, the second convex surface and the concave surface are formed, ensuring the precise implementation of subsequent steps and improving the appearance quality and consistency of the logo label.

[0009] First anode: The first color oxide film is formed by anodizing, so that the concave surface and the first convex surface are attached with the first color oxide film, and at the same time, it lays the foundation for subsequent laser engraving and secondary anode treatment.

[0010] First laser engraving: remove the first color oxide film on all surfaces except the first convex surface, the second convex surface and the concave surface, so that each part of the logo label can be processed with different colors, increasing the visual layering.

[0011] Second laser engraving: laser engrave the second convex surface to deepen its color and reach the color level required by the customer, and highlight the color difference between the first convex surface, the second convex surface and the concave surface, making the color of the logo label brighter and more beautiful.

[0012] Second anode: Through the second anodization, all surfaces except the concave surface and the first convex surface are coated with a second color oxide film, which further enhances the weather resistance and anti-fading properties of the logo and label. At the same time, the ink filling and ink removal processes are reduced, the production cycle is greatly shortened, and the production efficiency and yield rate are improved. At the same time, the protection of the second convex surface is strengthened to reduce the phenomenon of falling off. In this process, since the first color oxide film on the concave surface is not removed, it will not be affected when the second anodization is performed, and the color of the second convex surface is deepened again after the second anodization, making the first convex surface, the second convex surface and the concave surface more vivid, improving the beauty and quality of the car logo and label.

[0013] In summary, the present application is processed by milling, first anode, first laser engraving, second laser engraving, and second anode in sequence, so that the first convex surface, second convex surface, and concave surface are formed in different colors, making the color of the automobile logo more vivid, and in this process, there is no need to repeatedly inject ink and remove ink, saving steps, improving production efficiency, avoiding the impact on the oxide layer, and improving the yield rate of automobile logo production. And there is no need to process through printing, transfer and other processes, and it has better adhesion stability, reducing the possibility of falling off and wear, so that the automobile logo has better quality and production efficiency.

[0014] Preferably, the first color layer is bright silver; and the second color layer is gray.

[0015] By adopting the above technical solution, the first color is bright silver and the second color is gray, so that the color layers of the logo label are clear and the visual effect is more prominent. At the same time, the combination of bright silver and gray not only improves the overall aesthetics of the logo label, but also enhances the recognition of the logo. As the basic color, bright silver can maintain a good reflection effect under different lighting conditions, while gray can better set off the black color of the second convex surface, making the logo more three-dimensional and textured. In addition, this color combination can also effectively avoid the color fading problem that is prone to occur in traditional single-color logos during use, and extend the service life of the logo label.

[0016] Preferably, the milling step further comprises grinding the first convex surface and the second convex surface to make them flat to obtain a milled part.

[0017] By adopting the above technical solution, the first convex surface and the second convex surface are ground to make them flat, which can ensure the consistency and uniformity of subsequent anodizing and laser engraving steps, avoid color unevenness and processing defects caused by surface unevenness, and improve the quality and appearance consistency of the final product.

[0018] Preferably, the second anode step also includes highlight processing the side and highlight angle of the second laser engraved part, and then anodizing, so that all surfaces of the second laser engraved part except the concave surface and the first convex surface are coated with a second color oxide film, and the holes are sealed to obtain a car logo plate.

[0019] By adopting the above technical solution, the side and highlight angle of the second laser engraved part are subjected to highlight processing and then anodized, so that all surfaces of the second laser engraved part except the concave surface and the first convex surface are coated with a second color oxide film, and the holes are sealed to obtain the automobile logo plate. This process not only improves the color depth of the second convex surface, but also enhances the overall aesthetics and three-dimensional sense of the logo plate, and improves the visual effect of the product. At the same time, the highlight processing increases the smoothness and flatness of the logo plate surface, further improves the wear resistance and corrosion resistance of the product, and prolongs the service life. In addition, through this improvement, the complex processes of ink filling and ink removal in the traditional process are avoided, the production process is simplified, and the production efficiency and yield rate are significantly improved.

[0020] Preferably, the specific process in the first anode step is: degreasing the milled part for 1-5 minutes, alkali-processing for 5-30 seconds, chemically polishing for 5-15 seconds, and then anodizing for 50-70 minutes to form a first color oxide film on the surface of the milled part, sealing the pores for 50-70 minutes, and obtaining the first anode part.

[0021] By adopting the above technical solution, firstly, through the pretreatment steps such as degreasing, alkali treatment, and chemical polishing, the grease, impurities and tiny defects on the surface of the milled parts are effectively removed to ensure the uniformity and consistency of the subsequent anodizing process. The subsequent anodizing step forms a first color oxide film on the surface of the milled parts within 50-70 minutes, which improves the density and corrosion resistance of the oxide film. The sealing step further enhances the stability of the oxide film and prevents the performance of the oxide film from degrading due to environmental factors during use. The entire process not only improves the surface quality and aesthetics of the product, but also significantly improves production efficiency and yield rate.

[0022] Preferably, the second anodizing step also includes a dyeing and degreasing process, and the specific process is as follows: degreasing the second laser engraved part for 1-5 minutes, and then anodizing for 65-80 minutes, so that all surfaces of the second laser engraved part except the concave surface and the first convex surface are coated with a second color oxide film, and then dyeing for 10-20 seconds, sealing for 50-65 minutes, and obtaining a car logo plate.

[0023] By adopting the above technical solution, the oil stains on the surface of the second laser engraved part are first removed through the degreasing step to ensure the uniformity and integrity of the oxide film during the subsequent anodizing process. Then, anodizing is performed to coat all surfaces of the second laser engraved part except the concave surface and the first convex surface with a second color oxide film. This process not only improves the thickness and density of the oxide film, but also enhances the corrosion resistance and wear resistance of the oxide film. Subsequently, a dyeing step is performed to make the color of the second color oxide film more vivid and durable, thereby improving the aesthetics of the logo. Finally, a sealing step is performed to seal the micropores of the oxide film, further improving the protective performance and service life of the oxide film. The entire process reduces the ink filling and ink removal processes, improves production efficiency, reduces production costs, and ensures product quality and stability.

[0024] Preferably, the anodization in the second anodizing step uses an anodizing agent, and the anodizing agent is composed of the following weight percentages: Potassium Titanium Oxalate 0.1-0.5% Boric acid 0.01-0.03% Oxalic acid 3-5.5% Citric acid 0.5-0.8% Zinc nitrate 1.5-3.2% Sodium hexametaphosphate 0.01-0.03% Activation accelerator 0.2-0.5% The balance is water.

[0025] By adopting the above technical scheme, the effect and efficiency of anodizing can be significantly improved. Specifically, by using an anodizing agent with a specific ratio, a synergistic effect is produced between the components, which jointly promote the formation of an oxide film on the metal surface and the optimization of its properties. The addition of potassium titanium oxalate, boric acid, oxalic acid and citric acid improves the density and corrosion resistance of the oxide film, while enhancing the hardness and wear resistance of the oxide film. The addition of zinc nitrate and sodium hexametaphosphate further improves the uniformity and glossiness of the oxide film and enhances the overall performance of the oxide film. The use of an activation promoter accelerates the anodizing process, increases the formation rate of the oxide film, reduces the oxidation time, and thus improves production efficiency. In addition, the activation promoter also improves the adhesion and stability of the oxide film and reduces the risk of oxide film shedding. In summary, this technical scheme not only improves the production efficiency of automobile logo OEM, but also ensures the stability and reliability of product quality.

[0026] Preferably, the activation promoter is composed of the following raw materials in weight percentage: Tricarboxylic acid 59-68% Zinc Gluconate 12-25% Zinc stearate 10-15% Glutamic acid derivatives 5-10%.

[0027] By adopting the above technical scheme, the specific ratio of tricarboxylic acid, zinc gluconate, zinc stearate and glutamic acid derivatives in the activation promoter can significantly improve the formation rate and quality of the oxide film during the anodizing process. The tricarboxylic acid reacts chemically with the components in the metal oxide film, introduces new functional groups, and improves the surface properties of the oxide film. Zinc gluconate has a corrosion inhibition effect, improves the performance of the oxide film, promotes the anode reaction, and improves the stability and environmental protection of the electrolyte. Zinc stearate optimizes the performance of the electrolyte, improves the film quality, and enhances the adhesion between the brand body and the oxide film. Glutamic acid derivatives further improve the wettability and dispersibility of the electrolyte, and improve the efficiency and quality of anodizing. The synergistic effect of these components makes the final oxide film have better mechanical properties, corrosion resistance and aesthetics, thereby improving the overall quality and service life of the car logo plate.

[0028] Preferably, the tricarboxylic acid is one or more of cyclohexane tricarboxylic acid, propylene tricarboxylic acid, and 1,2,3,4-butane tetracarboxylic acid.

[0029] By adopting the above technical solution, one or more of cyclohexane triacid, propylene triacid, and 1,2,3,4-butane tetracarboxylic acid are selected as tricarboxylic acids, which can effectively improve the performance of the anodic oxidant. These carboxylates react chemically or interact with the components in the metal oxide film during the anodic oxidation process, introduce new functional groups or change the surface properties of the oxide film, thereby preparing a metal oxide film with special functions (such as hydrophilicity, hydrophobicity, biocompatibility, etc.). At the same time, they may also produce synergistic effects with other additives (such as inorganic salts, surfactants, corrosion inhibitors, etc.), further improving the efficiency and effect of anodic oxidation, so that the oxide film formed on the metal surface has better performance and a wider range of applications.

[0030] Preferably, the glutamate derivative is cocoyl glutamate and / or chitosan glutamate derivative.

[0031] By adopting the above technical scheme, using cocoyl glutamic acid and / or chitosan glutamic acid derivatives as glutamic acid derivatives, the wettability and dispersibility of the electrolyte can be significantly improved, and the efficiency and quality of anodic oxidation can be improved. The emulsification, solubilization and penetration capabilities of cocoyl glutamic acid help clean the anode surface, remove impurities and oil stains, and thus facilitate the formation of an oxide film. The excellent adsorption properties of chitosan glutamic acid derivatives help remove impurities and oil stains in the electrolyte, reduce defects on the anode surface, and improve the quality and performance of the oxide film.

[0032] In summary, the present application includes at least one of the following beneficial technical effects: 1. Through multi-step processes such as milling, anodizing and laser engraving, the first convex surface, the second convex surface and the concave surface of the logo label are made to present different colors, which effectively solves the problem of ink filling in the concave area in the traditional process, avoids the inefficiency and errors caused by manual operation, and improves production efficiency; 2. During the second anodizing process, the color of the second convex surface is significantly deepened by using special anodizing agents and activation promoters, reaching the black level required by customers, solving the problem of substandard color of RS fonts in laser engraving in traditional processes, and improving the visual effect and aesthetics of the product; 3. There is no need for ink filling and ink removal processes in the entire process, which reduces production steps, shortens production cycle, improves yield rate and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a structural schematic diagram of the automobile identification plate of this application. DETAILED DESCRIPTION

[0034] The following is combined with Figure 1 The present application is further described in detail with reference to the accompanying drawings and embodiments.

[0035] Sources of some raw materials: The anodizing solution in the first anode step includes 120 g / L sulfuric acid, 5 g / L LOP-10, 30 g / L silver ions, and water to volume; Example 1-3: The anodizing solution in the second anode step includes 120 g / L sulfuric acid, 5 g / L OP-10, 30 g / L zinc ions, and water to volume; Sealing agent: Brand model Shengyuan YASY-707, diluted 5 times; Degreasing agent: Shanghai Yinxi Industrial Co., Ltd., model FKES-284, diluted 10 times; The alkali solution is a sodium carbonate solution with a mass fraction of 5%; Polishing liquid: preferably from Wenzhou Aoyang Technology Co., Ltd., model OY-9C; Zinc gluconate: molecular formula C12H22O14Zn, molecular weight: 455.69; Cocoyl glutamate: CAS: 210357-12-3; Cyclohexanetrioic acid CAS 16526-68-4; Chitosan glutamic acid derivative CAS: 84563-76-8.

[0036] Preparation Example of Anodic Oxidant Preparation Example 1 An anodic oxidant is prepared by the following method: According to weight percentage, 0.1% of potassium titanium oxalate, 0.03% of boric acid, 3% of oxalic acid, 0.8% of citric acid, 1.5% of zinc nitrate, 0.01% of sodium hexametaphosphate, 0.2% of activation promoter and 94.36% of water were weighed and put into a stirring device. The mixture was stirred at a speed of 200 r / min for 10 minutes to fully mix the mixture and obtain an anode oxidizer.

[0037] In terms of weight percentage, the activation accelerator is obtained by uniformly mixing 68% of tricarboxylic acid, 12% of zinc gluconate, 10% of zinc stearate and 10% of glutamic acid derivative; wherein the tricarboxylic acid is cyclohexanetricarboxylic acid; and the glutamic acid derivative is coconut oil acyl glutamic acid.

[0038] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used is different, as shown in Table 1; Table 1 Raw material dosage of preparation examples 1-3 (%) Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 2 is that the tricarboxylic acid is propylene tricarboxylic acid.

[0039] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 2 is that the tricarboxylic acid is 1,2,3,4-butanetetracarboxylic acid.

[0040] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 2 is that the tricarboxylic acid is composed of cyclohexane triacid, propylene triacid, and 1,2,3,4-butane tetracarboxylic acid in a weight ratio of 1:2:1.

[0041] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 2 is that the glutamic acid derivative is a chitosan glutamic acid derivative.

[0042] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 2 is that the glutamic acid derivative consists of cocoyl glutamic acid and chitosan glutamic acid derivative in a weight ratio of 1:0.7.

[0043] Preparation Example Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the activation accelerator is replaced with citric acid in equal amount.

[0044] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of zinc gluconate is replaced by tricarboxylic acid.

[0045] Preparation Comparative Example 3 The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of zinc stearate is replaced by tricarboxylic acid.

[0046] Preparation Comparative Example 4 The difference between Preparation Comparative Example 4 and Preparation Example 1 is that an equal amount of glutamic acid derivative is replaced by a tricarboxylic acid. Example

[0047] Example 1 A method for preparing a car logo plate comprises the following steps: Milling: Process one side of the plate body made of 1050 aluminum material by a milling machine to form a first convex surface, a second convex surface and a concave surface on its surface to obtain a milled part; First anode: put the milling part into degreasing agent for degreasing for 3 minutes, then soak it in alkaline solution for 20 seconds, then soak it in polishing solution for chemical polishing for 10 seconds, then put it into the silver-containing anodizing solution electroplating tank for anodizing for 60 minutes at a voltage of 14V to form a first color oxide film on the surface of the milling part, then put it into the sealing agent for immersion and sealing for 60 minutes, rinse it with clean water, and then air-dry the surface moisture to obtain the first anode part; First laser engraving: laser engraving is performed by a laser engraving machine with the following parameters: angle 90 degrees, line spacing 0.025 mm, speed 250 mm / s, power 19 W, frequency 25 KHz, so that the first color oxide film on all surfaces of the first anode part except the first convex surface, the second convex surface and the concave surface is completely removed to obtain the first laser engraved part; Second laser engraving: laser engraving the second convex surface of the first laser engraved piece by a laser engraving machine, the laser engraving parameters are angle 45 degrees, line spacing 0.02mm, speed 150mm / s, power 54W, frequency 110KHz, laser engraving time 20s, so that the second convex surface is charred to form a dark color layer, the dark color layer is black, and the second laser engraved piece is obtained; Second anode: put the second laser engraved piece into the degreasing agent for 2 minutes, then put it into the electroplating tank of the anodizing liquid for 70 minutes of anodizing, the voltage is 13V, so that all surfaces of the second laser engraved piece except the concave surface and the first convex surface are plated with a second color oxide film, then put it into the sealing agent for 60 minutes of immersion sealing, rinse it with clean water, and then air dry the surface moisture to obtain the car logo plate. This car logo plate can refer to Figure 1 , the first color layer is bright silver; the second color layer is gray, and the dark color layer is black.

[0048] The milling step also includes grinding the first convex surface and the second convex surface to make them flat to obtain a milled part.

[0049] The second anode step also includes highlight processing the side and highlight angle of the second laser engraved part, and then anodizing, so that all surfaces of the second laser engraved part except the concave surface and the first convex surface are coated with a second color oxide film, and then placed in a sealing agent for sealing for 60 minutes, rinsed with clean water, and then air-dried to obtain a car logo label.

[0050] Example 2 The difference between Example 2 and Example 1 is that the process parameters are different; the details are as follows: The laser engraving parameters in the first laser engraving step are line spacing 0.015 mm, speed 200 mm / s, power 17 W, and frequency 23 KHz; the laser engraving parameters in the second laser engraving step are line spacing 0.025 mm, speed 100 mm / s, power 50 W, and frequency 120 KHz.

[0051] In the first anode step: degreasing for 1 min, alkali treatment for 30 s, chemical polishing for 15 s, anodizing for 70 min, and sealing for 50 min.

[0052] In the second anode step: degreasing for 5 min, anodizing for 65 min, and sealing for 50 min.

[0053] Example 3 The difference between Example 3 and Example 1 is that the process parameters are different; the details are as follows: The laser engraving parameters in the first laser engraving step are line spacing 0.015 mm, speed 150 mm / s, power 16 W, and frequency 20 KHz; the laser engraving parameters in the second laser engraving step are line spacing 0.015 mm, speed 200 mm / s, power 60 W, and frequency 100 KHz.

[0054] In the first anode step: degreasing for 5 min, alkali treatment for 5 s, chemical polishing for 5 s, anodizing for 50 min, and sealing for 70 min.

[0055] In the second anode step: degreasing for 1 min, anodizing for 80 min, and sealing for 50 min.

[0056] Embodiment 4-15 The difference between Example 4 and Example 1 is that the source of the anode oxidant in the second anode step is different, as shown in Table 2: Table 2 Sources of the anodic oxidant in the second anode step of Examples 4-15 Example 16 The difference between Example 16 and Example 1 is that: the second laser carved part is placed in a degreasing agent for degreasing for 2 minutes, and then the second laser carved part is placed in anodizing liquid for anodizing for 70 minutes at a voltage of 13V, so that all surfaces of the second laser carved part except the concave surface and the first convex surface are coated with a layer of second color oxide film, and then placed in a dye for immersion dyeing for 15 seconds, air-dried, and then placed in a sealing agent for immersion sealing for 60 minutes, rinsed with clean water, and then air-dried to obtain a car logo label.

[0057] The dyeing process is carried out according to the needs to meet the diversity of product colors.

[0058] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the second convex surface is processed into black by coating, which is as follows: The milling process and the first anode process remain unchanged; The second convex surface of the first anode member is coated with black ink and UV cured for 2 minutes to obtain a black second convex surface. German Gaoshi T300 N50 black ink.

[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that a thermal transfer method is used to process the second black convex surface. The specific process is as follows: The milling process remains unchanged; the milled part is degreased for 3 minutes, immersed in alkaline solution for 20 seconds, immersed in polishing liquid, chemically polished for 10 seconds, and then placed in a silver-containing anodizing solution electroplating tank for 60 minutes of anodizing at a voltage of 14V to form a first color oxide film on the surface of the milled part, which is then cleaned and air-dried to obtain a first anode part; a transfer film containing a black pattern is attached to the second convex surface of the first anode, and heated to 180°C for 250 seconds under a vacuum of -0.1MPa displayed on the vacuum gauge to transfer the black pattern to the second convex surface, and then placed in a sealing agent for immersion and sealing for 60 minutes, rinsed with clean water, and then air-dried to obtain a black second convex surface.

[0060] The transfer film with a black pattern is prepared by the following method: spraying German Gaoshi T300 N50 black ink on a thermal transfer film, and curing the film to obtain a transfer film containing a black pattern.

[0061] Performance testing Detection method / test method Colorimetry: The automobile identification plates obtained in Examples 1-16 and Comparative Examples 1-2 are tested using a colorimeter to compare the colors on the first convex surface, the second convex surface, and the concave surface with the colors on the sample. If the color difference values ​​are all less than 0.5, it is considered qualified; if they are greater than 0.5, it is considered unqualified.

[0062] Adhesion stability: The dark color layer obtained in the second anodic step was tested by the falling sand test method, the test standard was based on ASTM D968-09, and the amount of bottom see-through was recorded.

[0063] The specific data of the above data are shown in Table 3; Table 3 Examples 1-15 and Comparative Examples 1-2 Example Pass rate (%) Bottom penetration dosage (L) Example 1 90 33 Example 2 88 30 Example 3 87 31 Example 4 99 55 Example 5 100 57 Example 6 99 56 Example 7 99 57 Example 8 100 56 Example 9 100 60 Example 10 100 60 Embodiment 11 100 63 Example 12 93 45 Embodiment 13 93 48 Embodiment 14 94 50 Embodiment 15 95 51 Comparative Example 1 88 13 Comparative Example 2 81 21 Combining Example 1 and Comparative Examples 1-2 and Table 3, it can be seen that the adhesion stability of the dark color layer is increased by the process of the present application, which is higher than the coating method and thermal transfer method in Comparative Examples 1-2, and the product qualification rate is also higher. Therefore, it is shown that the preparation method of the present application can obtain higher product quality.

[0064] It can be seen from Example 1, Example 4, Examples 12-14 and Table 4 that the qualified rate and bottom penetration amount of Example 1 and Examples 12-14 are lower than the qualified rate and bottom penetration amount of Example 4, indicating that the present application uses tricarboxylic acid, zinc gluconate, zinc stearate, and glutamic acid derivatives as activation promoters, and combines potassium titanium oxalate, boric acid, oxalic acid, citric acid, zinc nitrate, sodium hexametaphosphate, etc. to obtain an anodic oxidant. During the anodizing process, a stable oxide film is easily formed on the surface of the second convex layer, and the process can protect the dark color layer and prevent it from falling off, thereby achieving a better effect.

[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a car logo plate, characterized in that: The following steps are involved: Milling: processing one side of the plate body to form a first convex surface, a second convex surface and a concave surface on its surface to obtain a milled part; First anode: clean the milled part, then perform anodization to form a first color oxide film on the surface of the milled part, seal the hole, and obtain the first anode part; First laser engraving: laser engraving all surfaces of the first anode part except the first convex surface, the second convex surface and the concave surface, and removing all the first color oxide film formed thereon to obtain a first laser engraved part; Second laser engraving: laser engraving the second convex surface of the first laser engraved piece so that the second convex surface forms a dark color layer to obtain a second laser engraved piece; Second anode: anodize the second laser engraved piece, so that all surfaces of the second laser engraved piece except the concave surface and the first convex surface are coated with a second color oxide film, and the holes are sealed to obtain a car logo plate.

2. The method for preparing a car logo plate according to claim 1, characterized in that: The laser engraving parameters in the first laser engraving step are angle 90 degrees, line spacing 0.015-0.035 mm, speed 150-250 mm / s, power 16-19 W, and frequency 20-25 KHz; the laser engraving parameters in the second laser engraving step are angle 45 degrees, line spacing 0.015-0.025 mm, speed 100-200 mm / s, power 50-60 W, and frequency 100-120 KHz.

3. The method for preparing a car logo plate according to claim 1, characterized in that: The milling step also includes grinding the first convex surface and the second convex surface to make them flat to obtain a milled part.

4. The method for preparing a car logo plate according to claim 1, characterized in that: The second anode step also includes highlight processing the side and highlight angle of the second laser engraved piece, and then anodizing, so that all surfaces of the second laser engraved piece except the concave surface and the first convex surface are coated with a second color oxide film, and the holes are sealed to obtain a car logo plate.

5. The method for preparing a car logo plate according to claim 1, characterized in that: The specific process in the first anode step is: degreasing the milled part for 1-5 minutes, alkali-processing for 5-30 seconds, chemically polishing for 5-15 seconds, and then anodizing for 50-70 minutes to form a first color oxide film on the surface of the milled part, sealing the pores for 50-70 minutes, and obtaining the first anode part.

6. The method for preparing a car logo plate according to claim 1, characterized in that: The second anodizing step also includes dyeing and degreasing processes, and the specific process is as follows: the second laser engraved part is degreased for 1-5 minutes, and then anodized for 65-80 minutes, so that all surfaces of the second laser engraved part except the concave surface and the first convex surface are coated with a second color oxide film, and then dyed for 10-20 seconds, and sealed for 50-65 minutes to obtain a car logo plate.

7. The method for preparing a car logo plate according to claim 1, characterized in that: The anodization in the second anode step uses an anodizing agent, and the anodizing agent is composed of the following weight percentages: Potassium Titanium Oxalate 0.1-0.5% Boric acid 0.01-0.03% Oxalic acid 3-5.5% Citric acid 0.5-0.8% Zinc nitrate 1.5-3.2% Sodium hexametaphosphate 0.01-0.03% Activation accelerator 0.2-0.5% The balance is water.

8. The method for preparing a car logo plate according to claim 1, characterized in that: The activation promoter is composed of the following raw materials in weight percentage: Tricarboxylic acid 59-68% Zinc Gluconate 12-25% Zinc stearate 10-15% Glutamic acid derivatives 5-10%.

9. The method for preparing a car logo plate according to claim 1, characterized in that: The tricarboxylic acid is one or more of cyclohexane tricarboxylic acid, propylene tricarboxylic acid, and 1,2,3,4-butane tetracarboxylic acid.

10. The method for preparing a car logo plate according to claim 1, characterized in that: The glutamic acid derivative is cocoyl glutamic acid and / or chitosan glutamic acid derivative.

Citation Information

Patent Citations

  • Metal identification piece and manufacturing method thereof

    CN101635117A

  • Surface treatment process for achieving 3D effect of electronic product

    CN105671615A

  • Workpiece surface treatment method and terminal shell

    CN108754569A

  • Surface treatment method for metal middle frame, metal middle frame and electronic equipment

    CN108790568A

  • Manufacturing method for double-color anodic oxidation

    CN112877743A